Genetic dissection of ion currents underlying all-or-none action potentials in C. elegans body-wall muscle cells - Liu, Ping (Blackwell Science Inc, 2011)
Although the neuromuscular system of C. elegans has been studied intensively, little is known about the properties of muscle action potentials (APs). By combining mutant analyses with in vivo electrophysiological recording techniques and Ca(2+) imaging, we have established the fundamental properties and molecular determinants of body-wall muscle APs. We show that, unlike mammalian skeletal muscle APs, C. elegans muscle APs occur in spontaneous trains, do not require the function of postsynaptic receptors, and are all-or-none overshooting events, rather than graded potentials as has been previously reported. Furthermore, we show that muscle APs depend on Ca(2+) entry through the L-type Ca(2+) channel EGL-19 with a contribution from the T-type Ca(2+) channel CCA-1. Both the Shaker K(+) channel SHK-1 and the Ca(2+)/Cl(−)-gated K(+) channel SLO-2 play important roles in controlling the speed of membrane repolarization, the amplitude of afterhyperpolarization (AHP) and the pattern of AP firing; SLO-2 is also important in setting the resting membrane potential. Finally, AP-elicited elevations of [Ca(2+)](i) require both EGL-19 and the ryanodine receptor UNC-68. Thus, like mammalian skeletal muscle, C. elegans body-wall myocytes generate all-or-none APs, which evoke Ca(2+) release from the sarcoplasmic reticulum (SR), although the specific ion channels used for AP upstroke and repolarization differ.